Analysis of the Criteria for Accepting Contribution Assistance (PBI) for the People of Medan City - Putri Ayu Syabrina Siregar; Marliyah Marliyah (Penerbit Jurnal Indonesia, 2022)
The aims of this research are (1) to find out how the Contribution Support Program (PBI) is implemented, and (2) to find out how the Contribution Support Program (PBI) is implemented National Health Insurance company in Medan City. , (3) To find out . Contribution Support Program Constraints. in Medan City. The author uses qualitative research to clarify this issue thoroughly. Then use data collection methods, observation techniques that involve direct observation and process, and document collection techniques that involve the process of obtaining information, information, and evidence. It is concluded that the results of this survey are elements of the implementation and standards of Contribution Assistance (PBI) in Medan City. Similarly, the distribution of state health insurance is thoroughly divided among the municipalities.